Autoformación de las ONG en transparencia y rendición de cuentas en Ecuador (Estudios) - Appe, Susan (2018)
The article focuses on the lack of EGONG programs in matters related to transparency and accountability in the case of Ecuador, and how the existing demand is being addressed by the organizations themselves but it is not being visualized by the university sector. Three principal discoveries are identified: first of all, generating alliances was essential to addressing the limited supply of formal EGONG programs; the potential for the replication of knowledge was one of the objectives on the studied process, and the evaluation of the processes of the programs was fundamental to energize new programs.